Análise geoambiental da degradação do sistema e subsistemas da microbacia hidrográfica do Riacho Carrapateiras-Tauá/CE - Gomes, Raul Carneiro (2015)
Environmental degradation is one of the major challenges that humanity has faced in favor of their survival and maintenance of ecological services. Therefore, the Hydrographic Basin (HB) has emerged as an environmental system and relevant planning unit for carrying out studies and construction of proposals towards its ecological management, to increase compatibility between the ability to support environmental and socio-activities productive. In semiarid regions, notably in the state of Ceará, the conservation of HB emerges as a strategic activity to mitigate environmental degradation, ensuring the maintenance of biodiversity, water availability, food and well-being of Ceará. So the Hydrographic Microbasin (HMB) of Carrapateiras stream was selected as the object of this research, which aims to analyze the environmental degradation of HMB cited and their subsystems through biophysical indicators. So, the systemic approach was employed in order to understand the elements and their procedural and functional interrelationships. Moreover, environmental surveys were made through fieldwork and collections of samples that were analyzed in situ and in laboratories. Therefore, it was found that, morphometric, MHB studied covers an area of 2.31 square kilometers, its main stream is 3.93 km long and its drainage density is 2.51 km.km-². It was found that the crystalline basement of the HMB consists of six rocks types involving amphibolites and granitoids and its reliefs are represented by tops, slopes, deep valleys and river plains. In addition, qualified-through 15 profiles the following pedologic taxa (Neossolos Litólicos, Neossolos Flúvicos, Cambissolos Háplicos, Luvissolos Pálicos e Luvissolos Órticos). Regarding the floristic survey have identified 93 phytospecies belonging to 33 families of vegetation classified as trees and shrubs Caatinga in secondary succession. From the analysis of interspecific degradation tops subsystems and Weaver saw slopes serra do Tecelão and Lagoa Seca/Coqueiros, it is concluded that the areas of transects T2 and T4 are the most degraded of the tops, while T2 is the most degraded area of mountain slopes cited respectively. The biophysical indicators used in interspecific analysis testified that the most degraded subsystem is fluvial plain. Thus, presently, the HMB is in environmental recovery pathways for lack of manpower, investment and abundant rainfall.